Piezoelectric properties in two-dimensional GeC and its surface functionalization by chlorination, fluorination, and chloro-fluorination. (September 2022) - Fakhrabad, Davoud Vahedi; Yeganeh, Mahboubeh
Abstract: In this work, the stability, mechanical, and piezoelectric properties of GeC monolayer and its alteration in halogenated GeC monolayers were investigated by density functional theory. The elastic parameters of GeC monolayer were reduced after halogenation, indicating the higher rigidity of the pure GeC monolayer in comparison to the halogenated ones. The relaxed-ion calculations revealed that the F-GeC-Cl and Cl-GeC-Cl configurations have the higher elastic stiffness, and higher e 11 compared with the Cl-GeC-F and F-GeC-F. The Hirshfeld charge analysis showed that the difference value between the charge of carbon atoms and the charge of halogen atoms are higher in Cl-GeC-F and F-GeC-F monolayers showing the electrons are more distributed around the halogen than the C atoms, and leading to the lower e 11 . The d 11 follows a similar pattern to e11 whereas the e 31 and d 31 almost follow the reverse pattern compared to the e 11 and d 11, and are almost larger when the electron is more distributed around the halogen atoms.